Prediction of mechanical properties such as strength and modulus using ultrasonic non‐destructive testing - Lim, Sian Yi (2019)
Metals such as aluminum and steel are typically malleable and ductile materials and it is important to know its current state and properties before allowing it to be implemented for its desired application. This report would present the results obtained from ultrasonic A, B and C scans on ASTM E-8 sub-size specimens together with the tensile tests. Tensile test was performed on the non-annealed specimens, followed by performing on the annealed specimens. Ultrasonic tests would then be executed on these specimens so that we can interpret and understand the signals produced, so that we can find out the degree of accuracy of results produced between ultrasonic testing and tensile testing. It is important to study the accuracy of these different tests as well as the different factors that might have affected the results produced. This study aims to possibly remove the requirement to do destructive tests on specimens upon uncovering the variations involved in the different tests performed and obtain an accurate approximation of the respective material E modulus.